Delež proti ciprofloksacinu odpornih klic Citrobacter freundii pri bolnikih z akutno levkemijo, ki prejemajo ciprofloksacin zaradi preprečevanja bakterijskih okužb - Strauch, Rika (Zdravniški vestnik, 2004)
Background. Authors tried to determine an efficiency of ciprofloxacin as infection prophylaxis in patients with acute leukaemia treated at the Department of Haematology in Clinical Center of Ljubljana. Due to cytotoxic chemotherapy, aplasia of bone marrow is inevitable. Therefore, these patients are at high risk for bacterial and fungal infection. The authors have noticed a rise in the number of ciprofloxacin-resistant strains of Citrobacter freundii and decided to find out if ciprofloxacin is still usable in this setting. Patients and methods. 45 patients with acute leukaemia were admitted to the Department of Haematology in the Clinical Center of Ljubljana during the year 2001 and 2002. All the patients received ciprofloxacin 2 x 500 mg on a daily basis. Citrobacter freundii was isolated in 11 patients, to whom we determined the proportion of ciprofloxacin-resistant strains of Citrobacter freundii and other Enterobacteriaceae. Susceptibility testing was done by the NCCCLS standards by the disc diffusion method and minimal inhibitory concentration. Results. C. freundii was isolated in 11 patients with AL. Extended-spectrum beta-lactamases (ESBL) C. freundii was isolated in 6 patients (54.5%). Ciprofloxacin-resistant C. freundii was isolated in 6 patients (54.5%). Six patients (54.5%) had ciprofloxacin-resistant C. freundiiwhich was ESBL positive at the same time. In AL patieuts with C. freundii (n = 11) almost half of isolated bacteria were Gram negative bacilli (45.2%, n=292), mostly from the family of Enterobacteriaceae. More than half of enterobacteria were ciprofloxacin-resistant, one third of them were also ESBL positive. Out of 131 enterobacteria, C. freundii was isolated 37 times. (28.2%). Conclusions. C. freundii was isolated in one fourth of AL patients. Half of the isolates were ciprofloxacin-resistant. The same was true for isolated enterobacteria. (Abstract truncated at 2000 characters).
Keywords: Ciprofloksacin; Ciprofloxacin; Citrobacter Freundii; Drug Resistance, Microbial; Drug Therapy; Enterobacteriaceae Infections; Enterobakteriacealne infekcije; Leukemia, Lymphocytic, Acute; Levkemija limfocitna, akutna; Microbial Sensitivity Tests; Mikrobni, občutljivostni testi; Prevention And Control; Therapeutic Use; Zdravilo, rezistenca mikrobna